Efficacy of Lopinavir/Ritonavir Compared With Standard Care for Treatment of Coronavirus Disease 2019 (COVID-19): A Systematic Review - Hariyanto, Timotius I.; Kristine, Elizabeth; Jillian Hardi, Catherine; Kurniawan, Andree (Infectious Disorders - Drug Targets, 2021)
Background: Coronavirus disease 2019 (COVID-19) is a newly discovered multi-organ disease caused by the novel coronavirus SARS-CoV-2. Currently, there are no official guidelines on the pharmacological treatment of COVID-19. Lopinavir/ritonavir is a licensed antiviral treatment against HIV and has shown activity against other coronaviruses. Objective: In this study, we review the evidence of the use of lopinavir/ritonavir as a potential treatment candidate against COVID-19. Methods: This systematic review has been registered in PROSPERO (CRD42020182067). A systematic search of the literature for the observational and randomized controlled trial was conducted in PubMed, PubMed Central, and Google Scholar through May 2nd, 2020. Two reviewers were independently searched and selected. The risk of bias was evaluated using the Jadad scale, Newcastle- Ottawa Quality assessment tool, and the National Institute of Health quality assessment tool. Results: A total of 1,965 articles were screened, from which 6 articles were selected. Of 6 articles that were included in this study, 4 reported no significant benefit in clinical improvement with lopinavir/ ritonavir when compared to standard care of treatment, while 2 studies reported otherwise. Lopinavir/ritonavir was also not associated with a reduction of 28-day mortality rate as reported by 1 included study. Most included studies reported gastrointestinal symptoms as side effects from lopinavir/ritonavir therapy. Conclusion: There is not yet enough evidence to support the regular use of lopinavir/ritonavir in the treatment of COVID-19. Further clinical trials are needed to evaluate lopinavir/ritonavir's efficacy in treatment.
Keywords: COVID-19